Conventional banks and Fintechs: how digitization has transformed both models. Issue 6 (6th November 2019) - Paulet, Elisabeth; Mavoori, Hareesh
Abstract : Purpose: The digital revolution has substantially changed the business environment. Most banks have acknowledged the importance of new technologies to improve performance and client satisfaction. The development of these innovations has led to the entrance of the so-called Fintechs. This paper aims to evaluate the impact of these transformations on the performance of financial institutions and on their business model. Design/methodology/approach: The authors use data envelopment analysis and Malmquist total productivity indices to measure financial institutions' efficiency and their influence on strategy. Findings: The main finding is that clients are more than ever at the core of banking strategy. The irrelevance of distance in basic banking transactions has reduced expenses and contributed to increasing revenues for all financial institutions. Banks will have a card to play in the advice they can bring to their clients. Practical implications: This research could be of interest for financial managers who wish to re-examine their current business practices and imagine their business model for the future. Originality/value: The contribution will be to further define the correlation between the provision of electronic banking services and its performance by including diversified institutions (conventional banks, Fintechs, Gafas) in the sample from multiple geographic zones to identify differences as regards their efficiency and business practices.